Is travel based residential self-selection a significant influence in modal choice and household location decisions?. (March 2019) - Humphreys, John; Ahern, Aoife
Abstract: This paper examines if residential self-selection can be observed in the population of the Greater Dublin Area and analyses the interactions that occur between travel choices and household location decisions. The research is based on data collected through a postal survey issued in April 2014. The paper outlines the differences observed in travel behaviour across contrasting land-use areas; with the findings showing higher use of sustainable modes for residents of denser, mixed-use urban areas with greater public transport options. Travel-based residential self-selection is a contributory factor to modal split characteristics but not to an extent that would invalidate the positive role of land-use measures in promoting sustainable travel. The study found that while transport is an important factor in choosing where to live, it is not the primary factor for all residents and its role is dependent on the characteristics of the respondent involved. The key conclusion is that residential self-selection does not occur to such an extent that it is more important than land-use factors in determining modal-split characteristics. However, it remains a significant contributory factor for certain populations when sustainable modes are considered. The paper highlights the importance of taking self-selection tendencies and housing characteristics into account when creating land-use-transport policies to reduce car dependency and discusses the role of the urban region in producing self-selection behaviour. Highlights: The key conclusion is that residential self-selection does not occur to such an extent that it is more important than land-use factors in determining modal-split characteristics. However, it remains a significant contributory factor for certain populations when sustainable modes are considered: younger people, renters, zero car households and those without children. The paper highlights the importance of taking self-selection tendencies and housing characteristics into account when creating land-use-transport policies to reduce car dependency and discusses the role of the urban region in producing self-selection behaviour.